Beyond Performance Status. Issue 9 (September 2020) - Simcock, R.; Wright, J.
Abstract: Oncologists should recognise the need to move beyond the Eastern Cooperative Oncology Group Performance Status (ECOG PS) score. ECOG PS is a longstanding and ubiquitous feature of oncology. It was evolved 40 years ago as an adaption of the 70-year-old Karnofsky performance score. It is short, easily understood and part of the global language of oncology. The wide prevalence of the ECOG PS attests to its proven utility and worth to help triage patient treatment. The ECOG PS is problematic. It is a unidimensional functional score. It is mostly physician assessed, subjective and therefore open to bias. It fails to account for multimorbidity, frailty or cognition. Too often the PS is recorded only once in wilful ignorance of a patient's changing physical state. As modern oncology offers an ever-widening array of therapies that are 'personalised' to tumour genotype, modern oncologists must strive to better define patient phenotype. Using a wider range of scoring and assessment tools, oncologists can identify deficits that may be reversed or steps taken to mitigate detrimental effects of treatment. These tools can function well to identify those patients who would benefit from comprehensive assessment. This overview identifies the strengths of ECOG PS but highlights the weaknesses and where these are supported by other measures. A strong recommendation is made here to move to routine use of the Clinical Frailty Score to start to triage patients and most appropriately design treatments and rehabilitation interventions.